IMPACT OF THE IDEAS OF BYZANTINIZATION ON ARTS IN GALICIA IN THE FIRST HALF OF THE TWENTIETH CENTURY - Kis’, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is about the influence of the ideas of vizantynism on Ukrainian sacral art in the first half of XX century. These processes were characterized by the attempt to use the folklore painting techniques, examples of folklore art and architecture in the high art.